2018
DOI: 10.1001/jamanetworkopen.2018.4707
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Humanitarian Pediatric Cardiac Surgery Programs in Low- and Middle-Income Countries

Abstract: Key Points Question Is humanitarian global pediatric cardiac surgery in low- and middle-income countries cost-effective? Findings This economic evaluation found that for a cohort of 424 children who underwent operations in 10 low- and middle-income countries in 2015, the cost-effectiveness of the intervention was $171 per disability-adjusted life-year averted. Meaning Humanitarian pediatric cardiac surgery in low- and middle-inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…The average cost per patient, including hospital discount, is $19,800 in our setting, whereas, in many developing countries, the reported cost of pediatric cardiac surgery is described within a range of $3.000-10.000 (22,27). This significant difference is due to the strategic decision taken by our program to model our pediatric cardiac surgery center using examples from the developed world, which incurs substantial costs related to maintenance, equipment, safety, training, excellent outcome measures, and appropriate salaries to retain the talented human resources.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The average cost per patient, including hospital discount, is $19,800 in our setting, whereas, in many developing countries, the reported cost of pediatric cardiac surgery is described within a range of $3.000-10.000 (22,27). This significant difference is due to the strategic decision taken by our program to model our pediatric cardiac surgery center using examples from the developed world, which incurs substantial costs related to maintenance, equipment, safety, training, excellent outcome measures, and appropriate salaries to retain the talented human resources.…”
Section: Discussionmentioning
confidence: 79%
“…Nevertheless, cardiac surgery for CHD remains an essential part of pediatric health care for the following considerations: ( 1 ) our profession's moral imperative is to treat these children, regardless of any financial concern; ( 2 ) denying care for children with CHD, would not improve the care of other diseases: due to inefficient governance, denying funds to CHD doesn't mean that these funds would be allocated to strengthen other health care issues; ( 3 ) according to the United Nations, treating CHD offers considerable economic value in terms of human development ( 22 , 23 ). In 2018, Cardarelli et al analyzed 446 patients operated in several low and middle-income countries to estimate the improvement in the United Nations Human Development Indicators for each survivor as a proxy for the long-term benefits of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that there is a role for these short-term missions. In a detailed study of the financial implications of their many short term missions to LMICs, Cardarelli et al have shown the cost effectiveness of intervention and the benefit to the society (14). In 2015, 446 patients received intervention in 10 LMICs at a total cost of $3,210,873.…”
Section: Short Term Medical Missionsmentioning
confidence: 99%
“…Cardiac surgery is expensive and largely inaccessible without comprehensive public or private health insurance or philanthropic support to carry the financial burden for patients. Despite concerns regarding costs of cardiac surgery in low- and middle-income countries (LMICs) and small island developing states (SIDS), initial data suggest favourable cost-effectiveness to establish and operate local cardiac centers in LMICs and SIDS alike [2] , [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%